English Teaching Techniques - Umurzakova Dilfuza Ilkhamovna; Salomova Farangiz Firdavsovna (Zien Journals, 2021)
There are various methods of teaching English. Teaching a foreign language, it is necessary to pay attention to new ways of stimulating students' speech. However, numerous classical schools still try to teach by the old methods and from the old books. There will always be problems and you will never speak English Good. By using new methods, it is easy to learn to speak English and improve at it. You will be able to speak like a native speaker.
Keywords: Methodology; English; teaching